Digital Banking Adoption Behaviour of Nepalese Customers - Shayastha Poudyal, (Nepalese Journal of Management Research, 2025)
Digital banking has become an integral part of the global financial landscape, offering convenience and accessibility to the customers. Through the availability of digital banking amenities customers can perform transaction 24/7. In Nepal, as well as other emerging economies, the adoption of digital banking platform is one of the crucial areas of the study. The research was solely based on the primary data which was allocated using the survey questionnaire. A sample of 345 respondents were undertaken where data were analyzed using two statistical software namely: IBM SPSS 25v and Smart-PLS 4.0. Based on the findings of the study the independent variables such as perceived usefulness, perceived ease of use, perceived credibility, subjective norms and awareness have significant impact on the adoption behaviour of general Nepalese customers while controlling variables like gender, age and educational qualifications do not significantly impact. The result of the study depicts that majority of the customers find digital banking amenities useful in their daily lifestyle whereas are afraid of the cyber threats and various fraudulent activities that are occurring due to which people are not able to fully trust the digital banking amenities in the 21st century too. Therefore, the banks and financial institutions need to emphasize more on providing strict security protocols and gaining the trust from the general public so that digitalized platforms are fully embraced by the general customers